Association between shiftwork and the risk of colorectal cancer in females: a population-based case–control study. Issue 5 (3rd February 2018) - Walasa, Wa Mwenga; Carey, Renee N; Si, Si; Fritschi, Lin; Heyworth, Jane S; Fernandez, Renae C; Boyle, Terry
Abstract : Objective: Research indicates that shiftwork may be associated with increased risks of adverse health outcomes, including some cancers. However, the evidence of an association between shiftwork and colorectal cancer risk is limited and inconclusive. Further, while several possible pathways through which shiftwork might result in cancer have been proposed, few studies have taken these factors into account. We investigated the association between two types of shiftwork (graveyard shiftwork and early-morning shiftwork) and six mechanistic shiftwork variables (including light at night and phase shift) and the risk of colorectal cancer among females in an Australian population-based case–control study. Graveyard shiftwork was the primary exposure of interest. Methods: Participants (350 cases and 410 controls) completed a lifetime occupational history, and exposure to each of the eight shiftwork variables was assigned to participants through a job exposure matrix. We used logistic regression to calculate odds ratios (OR) and corresponding 95% confidence intervals (CI) for the association between different shiftwork variables and the risk of colorectal cancer, adjusting for potential demographic, lifestyle and medical confounders. Results: Working in an occupation involving long-term exposure (>7.5 years) to graveyard shiftwork was not associated with colorectal cancer risk (adjusted OR 0.95, 95% CI 0.57 to 1.58). Similarly, no increased risks of colorectal cancer were seen for any of the other seven shiftwork variables examined. Conclusions: No evidence of an increased risk of colorectal cancer among females who had worked in occupations involving shiftwork was observed in this study.